2017
DOI: 10.1177/1352458517699289
|View full text |Cite
|
Sign up to set email alerts
|

Body size and physical exercise, and the risk of multiple sclerosis

Abstract: These findings add weight to evidence linking being overweight to an increased MS risk in men. Furthermore, they suggest that exercise may be an additional modifiable protective factor for MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 283 publications
(433 reference statements)
1
24
0
2
Order By: Relevance
“…Exercise training (ET) attenuates symptoms and delays the progression of disability in multiple sclerosis (MS) patients, while low levels of physical fitness have been suggested as a risk factor for developing MS . Accordingly, ET has been shown to modulate other autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis, inflammatory bowel disease, and others .…”
Section: Introductionmentioning
confidence: 99%
“…Exercise training (ET) attenuates symptoms and delays the progression of disability in multiple sclerosis (MS) patients, while low levels of physical fitness have been suggested as a risk factor for developing MS . Accordingly, ET has been shown to modulate other autoimmune diseases, such as systemic lupus erythematosus, rheumatoid arthritis, inflammatory bowel disease, and others .…”
Section: Introductionmentioning
confidence: 99%
“…(34) Generally, according to the current research, it can clearly be concluded that exercise can be the basis of treating patients with MS. It has been shown that any of the mentioned exercises can have a positive effect on all types of symptoms commonly seen in patients with MS. (35) Exercise leads to a significant improvement in life quality without any negative impact, because all studies that track adverse results didn't show an increase in the exacerbation of the disease or events. Note that it doesn't seem that exercise prevent or reduce the frequency of recurrence of the disease, but it improves endurance and coordination of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Selected controls were frequency-matched on year of birth from the Norwegian Conscript Service database (n=19,530). 7 The study found that men who developed relapsing MS symptoms up to 2 years following their cognitive assessment had significantly lower cognition scores compared with controls as did men who developed PPMS up to 20 years after their assessment, suggesting that cognitive problems may be present before apparent symptoms of MS. A second nested case-control study using the same Norwegian population-based database and MS registry found that a body mass index ≥25 was significantly associated with an increased risk of MS in men and that exercise may be a modifiable protective factor for MS. 8 The prodromal period for MS requires additional study to better characterize it and to recognize the progression to clinical MS.…”
Section: Clinical Course Of Multiple Sclerosismentioning
confidence: 99%